Adaptive predictive state-space control of a multivariable 3-tank system - Gambier, Adrián; Unbehauen, Heinz (Decision and Control, 1999 38th IEEE Conference On, 2002)
The real time results of an adaptive multivariable generalized state-space predictive controller are presented. The control algorithm consists of a state-space receding horizon tracking system, a compensator for piecewise constant random disturbances and an estimator for parameters, state and disturbances. The estimator is based on an augmented recursive identification algorithm.
Elektronische Reproduktion der Druckausgabe
Gesehen am 15.01.2020